An Analysis of Politeness Strategies in an English Textbook for University Students - Abd Ghofar; Gigih Dwiananto; Iman Jauhari; Aulia Noor Eliza (Universitas Kristen Cipta Wacana, 2026)
This study investigates the types and distribution of politeness expressions in an English textbook for university students in Indonesia. Drawing on Brown and Levinson's (1987) Politeness Theory as the analytical framework, the study employs a qualitative content analysis design to systematically identify and classify politeness expressions across the textbook's dialogue sections. A total of 121 utterances from nine dialogues were analyzed and categorized into four politeness strategies: Positive Politeness, Negative Politeness, Off-Record, and Bald On-Record. The findings reveal that Positive Politeness is the most dominant strategy (f = 77, 63.6%), followed by Off-Record (f = 17, 14.0%), Negative Politeness (f = 16, 13.2%), and Bald On-Record (f = 11, 9.1%). While all four strategies are represented in the textbook, their uneven distribution suggests it presents a pragmatically imbalanced model of English communication. These findings indicate that the textbook is primarily oriented toward solidarity-building and informal interaction, at the expense of preparing learners for formal, asymmetrical, and register-sensitive communicative contexts. The study concludes with recommendations for textbook developers and EFL practitioners to incorporate a more balanced and explicitly contextualized range of politeness strategies in university-level English instructional materials to foster socio-pragmatic competence for real-world communication.